2016
DOI: 10.1080/21675511.2016.1220468
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental models of transcription factor 4 deficiency converge on a common ion channel as a potential therapeutic target for Pitt Hopkins syndrome

Abstract: The clinically pleiotropic gene, Transcription Factor 4 (TCF4), is a broadly expressed basic helix-loop-helix (bHLH) transcription factor linked to multiple neurodevelopmental disorders, including schizophrenia, 18q deletion syndrome, and Pitt Hopkins syndrome (PTHS). In vivo suppression of Tcf4 by shRNA or mutation by CRISPR/Cas9 in the developing rat prefrontal cortex resulted in attenuated action potential output. To explain this intrinsic excitability deficit, we demonstrated that haploinsufficiency of TCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Individuals with PTHS have mild to severe motor learning impairments and often engage in stereotypic and repetitive movements such as hand clapping and flapping, repeated hand to mouth movements, head shaking, head banging, body rocking, washing, finger crossing, and rubbing toes together . Motor milestones and self‐care skills are delayed (see Section 10).…”
Section: Cognition and Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with PTHS have mild to severe motor learning impairments and often engage in stereotypic and repetitive movements such as hand clapping and flapping, repeated hand to mouth movements, head shaking, head banging, body rocking, washing, finger crossing, and rubbing toes together . Motor milestones and self‐care skills are delayed (see Section 10).…”
Section: Cognition and Behaviormentioning
confidence: 99%
“…Loss‐of‐function mutations in Tcf4 lead to the near‐complete lack of language acquisition. Language acquisition is virtually absent in most PTHS individuals . Up to 55% of individuals express only single words before 10 years of age, and indeed many have little to no expressive language throughout their lifespan ( R34 ).…”
Section: Cognition and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Originally generated as a model of constitutive germline deletion of one Tcf4 allele, our recent work has shown that a truncated TCF4 protein is in fact expressed in these mice[18]. Furthermore, we have shown this truncated protein is capable of binding to full length TCF4, confirming other previous reports that this transgenic PTHS mouse model may produce TCF4 haploinsufficiency through a dominant-negative binding mechanism[4, 18]. Although this model does not produce a complete allelic germline deletion, it still represents a powerful model for understanding PTHS biology, as the disruption of normal protein dimerization and DNA binding is a key element of the point mutations or other TCF4 gene disruptions that result in PTHS[4].…”
Section: Understanding Tcf4 Biologymentioning
confidence: 99%
“…Mutations have typically been reported in the bHLH domain where the possibility for disruption of normal E-protein binding function is high[1, 4, 12, 1517]. Not all mutations result in complete loss of TCF4 protein function, and evidence for dominant-negative effects of mutant protein has been observed[4, 18]. Reported PTHS-linked mutations that are located outside of this bHLH region have not been shown to lead to functional deficiencies in TCF4 protein, and how they result in disease remains an open question [4].…”
Section: Introductionmentioning
confidence: 99%